PENEGAKAN HUKUM TERHADAP PRAKTIK IUU FISHING DI PERAIRAN ZEE INDONESIA MENURUT UNCLOS 1982 (STUDI KASUS RUN ZENG 03 DAN 05): Law Enforcement Against Iuu Fishing Practices In Indonesia's Eez Under Unclos 1982 (Case Study: Run Zeng 03 And 05 Vessels) - Thovas Anugrah Iman; Yulia Fitriliani (Faculty of Law, Universitas Trisakti, 2025)
Indonesia, as the world’s largest archipelagic state, has a vast Exclusive Economic Zone (EEZ) rich in fishery resources. However, this also makes Indonesia's EEZ vulnerable to Illegal, Unreported, and Unregulated (IUU) Fishing by foreign vessels. This study examines the IUU Fishing practices by Run Zeng 03 and 05, along with Indonesia’s legal enforcement under the United Nations Convention on the Law of the Sea (UNCLOS) 1982. Using a normative juridical method with a descriptive and qualitative approach, this research finds that both vessels committed illegal and unreported fishing by operating without permits and failing to report their catch. These actions violated several provisions of UNCLOS 1982, including Articles 56, 58, 61, 62, 73, 192, and 193. Indonesia has exercised its coastal state rights by conducting arrests, seizures, and prosecution. However, the five-year imprisonment sentence given to Run Zeng 03’s captain by the Tual District Court contradicts Article 73(3) of UNCLOS 1982, which prohibits custodial penalties for fisheries violations in the EEZ. These findings highlight the urgency of harmonizing national law with international obligations to ensure compliance with the law of the sea.